Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Organization Citizenship Behavior Serta Kinerja Guru (Sebagai Variabel Intervening) Madrasah Aliyah (MA) Di Kabupaten Kendal - Prayuda Nur Rifki; Ahmad Shofi Mubarok (Journal on Education, 2024)
The purpose of this research is to examine and analyze the simultaneous and partial influence of Transformational Leadership, Organizational Culture, and Organizational Citizenship Behavior on teacher performance. This type of research is quantitative which explains the influence of the variables Transformational Leadership, Organizational Culture, and Organizational Citizenship Behavior on the performance of Madrasah Aliyah (MA) teachers in Kendal Regency. The population in this study was 109 people. The sampling technique uses purposive sampling. The data collection method is through scale distribution in the form of Likert model countries. The data analysis technique was carried out using multiple linear regression techniques. The results of this research show data that the F test shows 0.461 > 0.05 and the calculated F value is 0.867 > 2.69 and the significance is 0.001 which means it is smaller than alpha (α) – 0.05. So it can be concluded that H0 is rejected and H1 is accepted, meaning that the first hypothesis (H1) in this study is accepted. So that transformational leadership, organizational culture and organizational citizenship behavior have a significant effect on teacher performance.